Contribution of education, employment, and ethnicity level to the integration of Islam and Christian religions in Central Lampung regency - Sudarman Sudarman (IAIN Salatiga, 2021)
This study explores data on the contribution of level of education, employment, and ethnicity to the integration of Muslims and Christians in Central Lampung, by looking at the sociological dynamics of integration between adherents of Islam and those of Christianity. The group integration is divided into two—majorityminority and balanced group—based on religious adherence. Data were collected using observation, interviews, and questionnaires consisting of favorable and unfavorable. The data collected were analyzed quantitatively and qualitatively. Quantitative analysis was carried out using one-way analysis of variance, while qualitative analysis was adopted logical thinking, including induction, deduction, analogy, and comparison. The results of the study show that there are differences in integration between groups of people with a composition of minority-majority and balanced religious adherents that the majority-minority community group has a higher quality of integration than the balanced group. The education variable shows that the level of education has a positive correlation with the level of integration; the higher the education, the higher the quality of integration. The job variable does not have a significant effect, but the overall average value is above the hypothetical average value. Ethnic variables show variations in the quality of integration; Batak and Javanese ethnicities have high integration quality; Palembang ethnicity is moderate and Lampung ethnic has low integration quality. The integration of Muslims and Christians in Central Lampung is formed by group awareness, complementary subsystems and the presence of institutions, which become catalysts so that mechanical solidarity is formed. Differences between them are recognized but not given important meaning in the relationship between them.